Design and Build Special Service Tools for Remove & Install Drive Shaft for Komatsu HD785-7 Dump Truck - Reza Febriano Armas; Ari Aryadi; Rasma; Nugroho Putra Pratama (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2024)
One of the repair works on the Power Train Havy Dum Truck (HD 787-5) unit is general overhaul work, which includes replacing components or overhauling the final drive assembly unit. The solution to the uninstallation and installation work is to replace the final drive. The disassembly and assembly work process has a level of difficulty, so technicians need precision and accuracy in assembling the drive shaft on the final drive so that the time for this work process requires a long lead time. components) and has potential K3 hazards for technicians (manpower). The difficulty of inserting the drive shaft into the differential gear and rotating the ring gear in the final drive is a problem due to the long processing time. The innovation carried out is how to position the drift shaft parallel to the position of the differential gear, thus requiring a special tool to leverage and at the same time to rotate the drive shaft so that it can change the position of the position, with this leverage and position change effort it can speed up the removal and installation process and working time technicians are more effective and efficient in terms of labor costs on general overhaul work. One of the repair works on the Power Train Havy Dum Truck (HD 787-5) unit is general overhaul work, which includes replacing components or overhauling the final drive assembly unit. The solution to the uninstallation and installation work is to replace the final drive. The disassembly and assembly work process has a level of difficulty, so technicians need precision and accuracy in assembling the drive shaft on the final drive so that the time for this work process requires a long lead time. components) and has potential K3 hazards for technicians (manpower). The difficulty of inserting the drive shaft into the differential gear and rotating the ring gear in the final drive is a problem due to the long processing time. The innovation carried out is how to position the drift shaft parallel to the position of the differential gear, thus requiring a special tool to leverage and at the same time to rotate the drive shaft so that it can change the position of the position, with this leverage and position change effort it can speed up the removal and installation process and working time technicians are more effective and efficient in terms of labor costs on general overhaul work.